2020
DOI: 10.1292/jvms.19-0378
|View full text |Cite
|
Sign up to set email alerts
|

Identification of disordered metabolic networks in postpartum dairy cows with left displacement of the abomasum through integrated metabolomics and pathway analyses

Abstract: High-producing dairy cows are easily affected by left displacement of the abomasum (LDA) within 4 weeks postpartum. Although LDA is highly associated with metabolic disturbances, the related information on comprehensive metabolic changes, with the exception of some blood biochemical parameters, remains limited. In this study, the changes in plasma metabolites and in the metabolic profile of postpartum dairy cows with LDA were investigated through liquid chromatography coupled with quadrupole time of flight mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 50 publications
1
11
0
1
Order By: Relevance
“…Previous studies, and the present results, indicate that LDA cows experience severe metabolic stress, includ- ing a significant increase in lipid metabolism (Hostens et al, 2012;Klevenhusen et al, 2015;Overton et al, 2017). In addition to NEFA and BHB, studies have also reported a significant increase in the plasma levels of stearic acid, oleic acid, palmitic acid, myristic acid, and arachidonic acid (ARA) in LDA cows (Guo et al, 2020). Changes in these long-chain fatty acids indicate an intensification of lipid metabolism in the body and have also been reported during calving and NEB in dairy cows (Zhang et al, 2013;Loften et al, 2014;Luo et al, 2019).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Previous studies, and the present results, indicate that LDA cows experience severe metabolic stress, includ- ing a significant increase in lipid metabolism (Hostens et al, 2012;Klevenhusen et al, 2015;Overton et al, 2017). In addition to NEFA and BHB, studies have also reported a significant increase in the plasma levels of stearic acid, oleic acid, palmitic acid, myristic acid, and arachidonic acid (ARA) in LDA cows (Guo et al, 2020). Changes in these long-chain fatty acids indicate an intensification of lipid metabolism in the body and have also been reported during calving and NEB in dairy cows (Zhang et al, 2013;Loften et al, 2014;Luo et al, 2019).…”
Section: Discussionsupporting
confidence: 69%
“…To date, although researchers have studied the metabolic changes in cows with LDA based on nuclear magnetic resonance and liquid chromatography-mass spectrometry (Liu et al, 2015;Guo et al, 2020), few studies have investigated the metabolic changes in cows with LDA following surgery. We hypothesized that LDA in dairy cows would result in metabolic changes in plasma, compared with healthy cows, and that these metabolic changes would be reversed after surgical treatment of the LDA cows.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics is now widely used to explain the metabolic processes of dairy cows in disease events ( 15 ). Metabolic profiles of cows with LDA have demonstrated marked decreases in amino acid levels in the serum or plasma, including tryptophan, leucine, tyrosine, and isoleucine ( 7 , 16 ), which may be related to a nutrient deficit during the LDA event which reduces the size of the amino acid pool. Thus, knowledge of the amino acid pool and composition can provide insight into the changes in amino acid metabolism in dairy cows with LDA.…”
Section: Introductionmentioning
confidence: 99%
“…Por tanto, su condición es crítica y requiere tratamiento urgente (Mulon et al, 2006). Esta patología presenta una incidencia por lactancia de 0.3 a 6.3% estimando las pérdidas económicas en USD $340/caso, incluyendo pérdida de PL y el costo de la cirugía (Guo et al, 2020).…”
Section: Adaptaciones Metabólicasunclassified